Ngudari Reribet: Mulur-Mungkret dan Tatag Janda Muda Ditinggal Mati dalam Perspektif Ki Ageng Suryomentaram - Heru Sumbodo; Koentjoro Koentjoro (Gadjah Mada Journal of Psychology (GamaJoP), 2018)
Widowhood is a major problem for women. This research intends to analyze phenomenologically the young widow is left behind in the perspective of Ki Ageng Suryomentaram. The aim of this study; First, deeply analyze the young widows left dead on mulur-mungkret according to Ki Ageng Suryomentaram perspective. Second, to analyze in-depth tatag young widow left behind according to perspective Ki Ageng Suryomentaram. Criteria of the subject, first, women who became widows and have aged 30-45 years. Second, the subject is a widow under 6 months. The results showed that, firstly, the self-regulation the developed subject is still largely on the mind and body. Both are done with the thought that his life improved, and followed by adding skills to support the independence of his life. The three subjects have not arrived at Olah raos to place the problem more clearly and clearly. The three subjects have not really sumeleh (sincere). The steps are taken to reduce reribet limited to out of problems, not yet to understand their self.